Aplicación de presunción de la relación de trabajo y el principio de la primacía de la realidad sobre las formas en los contratos de prestación de servicios en Colombia (2025)
In Colombia there are many factors that violate human rights in labor matters. However, the Constitutional Court in different rulings states “Work is a human right, since it is a manifestation of man's freedom and therefore ultimately has its basis in the dignity of the human person” (Sentence T-008, 1992, p. 9). That is why the importance of this research to answer the question of how to apply the Presumption of the Employment Relationship and the Principle of the Primacy of Reality over Forms in Service Contracts in Colombia, There is a great problem at present in the private and public sector, where workers or contractors have been affected when in some cases employers or contractors through the modality of service contracts or outsourcing simulate and commit fraud to the law, camouflaging a real labor relationship by evidencing the three elements: personal provision of services, subordination of the worker to the employer and salary as remuneration (CST, 1950, Art. 23). In the present investigation a socio-legal methodology was used, with documentary analysis and normative and jurisprudential interpretation and it is concluded that when the principle of the primacy of reality over (CPC,1991, Art. 53), is complied with, in a labor relationship regardless of the name or denomination given to the contract or its denial, it is considered a fraud of the law.